Dosimetric parameters predictive of nasolacrimal duct obstruction after carbon-ion radiotherapy for head and neck carcinoma. (December 2019) - Kubo, Nobuteru; Kubota, Yoshiki; Kawamura, Hidemasa; Oike, Takahiro; Sakai, Makoto; Kumazawa, Takuya; Miyasaka, Yuhei; Okazaki, Shohei; Kobayashi, Daijiro; Sato, Hiro; Mizukami, Tatsuji; Musha, Atsushi; et al.
Highlights: Incidence of ND obstruction was 46% (13/28) for Grade 1 and 7% (2/28) for Grade 2. High ND volumes receiving 10–60 Gy(RBE) were associated with ND obstruction. Cutoff values classified obstruction-positive patients with >96% accuracy. Abstract: Background and purpose: Little information is available on the risk factors for nasolacrimal duct obstruction after radiotherapy for head and neck tumors. We investigated the incidence and predictive dosimetric parameters for nasolacrimal duct obstruction following carbon-ion radiotherapy for head and neck tumors. Materials and methods: Twenty-eight patients with head and neck non-squamous cell carcinoma were analyzed in this single-institution prospective study. More than half of the tumors were located in the nasal cavity and maxillary sinus. Carbon-ion radiotherapy consisting of 57.6 or 64.0 Gy(relative biological effectiveness; RBE) in 16 fractions was administered. Nasolacrimal duct obstruction was recorded according to Common Terminology Criteria for Adverse Events version 4.0. Cutoff values were determined using receiver operating characteristic (ROC) curve analysis. VX indicates the volume irradiated with X Gy(RBE). Results: The median follow-up period was 60.3 months. Incidences of Grade 1 and 2 nasolacrimal duct obstructions were 46% (13/28) and 7% (2/28), respectively; no Grade 3 or greater toxicities were recorded. Throughout the dose range, the volumes of the irradiated nasolacrimal ducts were significantly higher in the obstruction-positive patients than in the obstruction-negative patients ( p < 0.001 for V10, V20, V30, V40, V50, and V60). Cutoff values determined by the ROC curve analysis classified the obstruction-positive patients with an accuracy of >96% over the entire range of V10–V60. Conclusion: The incidence and predictive dosimetric parameters for nasolacrimal duct obstruction after carbon-ion radiotherapy were demonstrated in a prospective cohort. These data should help optimize carbon-ion radiotherapy treatments for patients with head and neck tumors.